Formulation of Antibacterial Liquid Soap Based on Virgin Coconut Oil with Various Concentrations of Carica Concentrate and Potassium Hydroxide Volume - Dianti, Siti; Kusumayanti, Heny (Journal of Vocational Studies on Applied Research, 2022)
Carica is one of the main commodities in Dieng, Central Java. It contains vitamin A, vitamin C, and antibacterial substances such as flavonoid, polifenol, and tannin. Due to its content, carica can be used as an additive for soap products.  Soap is one of the cosmetic products, produced from the saponification reaction between alkali and fatty acids. Carica liquid soap was carried out by  reacting KOH with virgin coconut oil that contains fatty acids, then adding carica fruit juice and other ingredients. The product of liquid soap will be analyzed including pH, density, free fatty acids content, organoleptic test, and antibacterial activity. The research method used is a factorial design. Research has shown that the carica liquid soap were in accordance with SNI 06-4075-1996 and SNI 06-3532-1994. The best quality of  carica liquid soap obtained at pH 11, density 1,0266, and free fatty acid content of 0,082%. Antibacterial activity was carried out using the paper disk method, showing that the antibacterial activity of the soap has a weak performances with an inhibition zone of 1,25 mm. The organoleptic test showed that panelist’s preference for carica liquid soap was low.